DEVELOPMENT GAP: LAND TRIBE IN SADAP VILLAGE REMPANG CATE VILLAGE GALANG DISTRICT BATAM CITY - Rahmawati, Nanik; Yulianda, Ririn Hersa; Valentina, Annissa (Gema Kampus IISIP YAPIS Biak, 2025)
Development gaps are often associated with poverty, underdevelopment, marginalization and their deprived lives, one of which is experienced by marginalized groups, namely the Land Tribe. The Darat tribe is a nomadic group that was then relocated to Kampung Sadap in 1973 through the policy of the Isolated Community Welfare Development Program (PKMT). The Darat Tribe was relocated to Kampung Sadap, where previously they were spread across Batam City so that currently all the Darat Tribe live in Kampung Sadap which is far from the city center. Therefore, this study aims to describe how marginal forms occur. This study uses qualitative research methods, the informants in this study are 7 people who were selected through purposive sampling techniques, and use data collection techniques in the form of interviews, observations and documentation. Then using Beall and Pirron's social exclusion theory as an analysis knife, and data analysis techniques using data reduction, data presentation and drawing conclusions. The results of this study show that the Land Tribe experiences marginalization in various aspects, the first is the social aspect such as in terms of uneven infrastructure development, namely roads, electricity, water and sanitation, access to education, unsuitable living conditions, uneven access to social assistance, the second is political aspect such as participation in decision-making and the third is economic aspect such as access to employment.